A Preliminary Study on Tsunami Disaster in Yogyakarta: Identification of Vulnerability Order and Components - Lina Wahyuni; Muh. Aris Marfai; M. Pramono Hadi (Department of Geography Education, University of Jember, 2020)
A tsunami is a disaster that can be hardly estimated. It is a significant concern UN since more than 60% of the world's population lives in coastal areas prone to tsunamis, including Indonesia. The county community with complex and dynamic plate requires mastering of mitigation strategies as a tsunami preventive effort. Understanding the vulnerable elements in risky areas is critical. However, the magnitude of potential disasters cannot be minimized. This study analyzes the tsunami vulnerability in Bantul, Special Region of Yogyakarta (DIY). The analysis was based on a description of assessment parameters such as land use, the physical condition of the area, social conditions, and availability of infrastructure. The results show that social vulnerability had the most significant impact. Keywords: Vulnerability, Tsunami, Bantul, DIY Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License